Case report: Two unique nonsense mutations in HTRA1-related cerebral small vessel disease in a Chinese population and literature review - Chen, Weijie; Wang, Yuanyuan; Huang, Shengwen; Yang, Xiaoli; Shen, Liwei; Wu, Danhong (Frontiers in Neurology, 2022)
Background: Homozygous or compound heterozygous mutations in the high-temperature requirement A serine protease 1 gene (HTRA1) elicits cerebral autosomal recessive arteriopathy with subcortical infarcts and white matter lesions (CARASIL). The relationship between some heterozygous mutations, most of which are missense ones, and the occurrence of cerebral small vessel diseases (CSVD) has been reported. Recently, heterozygous HTRA1 nonsense mutations have been recognized to be pathogenic. Case presentation: We described two Chinese patients diagnosed with HTRA1-CSVD accompanied by heterozygous nonsense mutations. Their first clinical manifestations were symptoms due to ischemic stroke and brain Magnetic Resonance Imaging (MRI) showed diffuse white matter lesions (WMLs) and microbleeds in both of them. Genetic sequencing revealed two novel heterozygous nonsense mutations: c.1096G >T (p.E366X) and c.151G>T (p.E51X). Conclusions: This case report expands the clinical, radiographic, and genetic spectrum of HTRA1-CSVD. Attention should be paid to young patients with ischemic stroke as the first clinical manifestation. Genetic screening for such sporadic CSVD is recommended, even if the symptoms are atypical.